The effect of types and concentrations of auxins on callus induction of Centella asiatica - SUCI RAHAYU; IKA ROOSTIKA; NURLIANI BERMAWIE (Nusantara Bioscience, 2016)
Abstract.  Rahayu S, Ika Roostika I, Bermawie N. 2016. The effect of types and concentrations of auxins on callus induction of Centella asiatica. Nusantara Bioscience 8:  283-287. Centella (Centella asiatica L.) is one of medicinal crops that have various utility as healing wounds, inflammation, rheumatic, hemorrhoids, tuberculosis, dysentery, leprosy, and fever and also as appetizer. In recent years the demand for raw materials of medicinal from Centella has increased. Until now, Centella has been harvested directly from nature without replanting so that this plant was worried to be extinct gradually. In vitro culture is one of the techniques for plant propagation. This technique has proved to be able to propagate a plant in large numbers, short time and uniform. Callus induction is initial stages of plant propagation by indirect organogenesis and somatic embryogenesis. The objectives of this research were to find out the most suitable type of auxins and its concentrations to induce callus formation of Centella. Explants used in this research were leaves and petioles taken from sterile culture of Centella var. Castina 1. Three kinds of auxins were used to this research, i.e. 2,4-D, Picloram and Dicamba at the levels of 2, 4 and 6 mgL-1. The result indicated that the most suitable type of auxin for inducing callus formation was 2,4-D or Dicamba at concentration of 4 mgL-1 which gave the highest percentage of callus formation, and the highest fresh weight as well.